The quality of bitterness in beer - Oladokun, Olayide (2017)
The bitterness of beer remains one of its most important flavour attribute. However, complexity surrounding bitterness perception alone represents a significant challenge in its understanding, in addition to other factors relating to production processes and raw materials used in making beer. The aim of this research was to better understand beer bitterness in terms of its intensity and quality, and how hopping technology (e.g. quantity and time of hop addition during the brewing process), hop aroma and variety may effect perceived bitterness intensity and quality. This project combined both analytical and sensorial analysis, and used statistical techniques to identify the key compounds driving bitterness perception. Analytical techniques were employed to quantify bitterness-contributing compounds and analytical bitterness units in beers alongside descriptive analysis of perceived sensory bitterness. Perceived sensory bitterness (both qualitative and quantitative) was assessed using a purpose developed list of well-defined bitterness attributes, to aid the characterisation of bitterness quality in beers. The impact of cross-modal flavour interactions on the perception of beer bitterness intensity and qualities was also investigated at varying analytical bitterness levels. Lastly, the effect of hop variety, and how this significant raw material affects perceived bitterness quality was also investigated using three distinctively different hop varieties (Hersbrucker, East Kent Goldings and Zeus). Results revealed a significant impact of the analytical profiles of beers, derived from the type of hop products and hopping technology adopted in beer production, on the perceived bitterness quality of beer. In general, beers high in hop acid compounds and polyphenols were, as expected, perceived to be higher in bitterness intensity. The results further showed that bitterness intensity also played a role in the perception of bitterness quality i.e. whether the beer was ‘harsh’, ‘lingering’ or ‘round’. However, beers high in these compounds were not always of ‘negative’ bitterness quality, and correspondingly lower amounts of these compounds did not always result in ‘positive’ bitterness qualities in beer. Results on the impact of cross-modal flavour interactions showed that hop aroma plays a crucial role in beer bitterness perception, and can modify the perception of bitterness intensity and quality as well as temporal profiles of bitterness in beer depending on analytical bitterness levels. The investigation into the impact of hop variety on perceived bitterness quality revealed hop-derived bitterness profiles relating to individual hop varieties, and further suggests that careful selection of the hop variety used for brewing is important for controlling perceived bitterness quality. This research provides a comprehensive interdisciplinary approach to understanding perceived beer bitterness and its associated qualities, with findings suggesting that besides bitterness intensity, the quality and overall impression of bitterness as perceived by consumers are significantly influenced by raw materials, production processes and other factors such as aroma which might be overlooked by brewers - but are likely to be significant for consumer preference and the success of a brand.